Aspects of Legal Protection Against Children Due to Acts of Psychological Violence (Bullying) in Karawang Vocational School Are Linked to The Rights of Children According to Law Number 35 Of 2014 on Child Protection - Ricky Herlana; Erlena Erlena (International Journal of Science and Applied Science: Conference Series, 2021)
Compared to children who are victims of abandonment, child victims of violence often get less public attention seriously because the suffering experienced by the victim is not as dramatic as those abandoned children. Violence is often identified with visible violence, such as physical and sexual violence. Though the violence that is psychological and social (structural) also bring a bad and permanent impact on the child.This study examines How Legal Protection Against Children From Violent Actions (Bullying) Is Linked With Child Rights According to Law No. 35 of 2014 on Child Protection. How Law Enforcement In Karawang district Service Protection Program Against Children Victims of Bullying and How Efforts  Provincial Health Karawang In Implementation Protection Against Children Victims of Violence. This research is conducted by normative juridical, with qualitative method and directed to analysis of Legal Protection of Children From Bullying, and use secondary data that is data obtained from library materials. Based on the research results can be concluded, that There are two forms of protection against students of bullying: First, Prevention of bullying. Second, Protection against victims of bullying. In addition to the protection of students who are preventive, there is also protection of students bullying victims.. Law enforcement conducted in the service of protection programs against child victims of bulliying, conducted by the Regional Police Karawang regency in preventing and cracking down on bullying by doing preventive and repressive actions.